Analisis Kualitas Layanan Website Pada Universitas Terbuka Palembang Menggunakan Metode Webqual 4.0 Dan Importance Performance Analysis (IPA) - Obi Mardalena; Ria Andryani (Journal of Information System and Informatics, 2021)
Website is a medium that is currently widely used as a tool to provide services and information. Palembang Open University is one of the universities that uses the website as a means to provide information related to academic activities to its students. To determine the quality of a website, it is necessary to analyze the measurement of website quality based on user perceptions. The purpose of this Analysis is used to determine the indicators that affect the quality of website services based on the instrument used from the webqual 4.0 method which consists of 3 variables, namely usability, information quality, and service interaction quality. Then the analytical technique used is importance performance Analysis (IPA) which will provide an overview of the indicators that need improvement or need to be maintained. The data collection technique in this study used a questionnaire with a research sample of 100 respondents. The results of the Analysis of the quality of website services at the Open University of Palembang have a suitability level of 99.99% or <100%. While the results of the average value of the gap (GAP) have a value of -0.01 which means that the quality of website performance has not fully met user expectations. Then the results of the Analysis of the IPA quadrant that need improvement because this quadrant has a low level of performance, so it can affect the level of interest of users to rely on these indicators, namely in the first priority quadrant which is indicator number 14 detailed information, indicator number 15 information in a format that according to indicator number 17 the website is safe from viruses.